Castle in Bezławki and its Alleged Administrative Functions - Kwiatkowski, Krzysztof (Studia Warmińskie, 2021)
The presented article negates the administrative function of the castle in Bezławki (Germ. Bäslack), which was attributed to it in the older literature (i.a. K.H. Clasen, F. Benninghoven, T. Torbus, Ch. Herrmann) – the researchers usually saw the stronghold as the seat of a local bailiff (Germ. Kämmerer). In the absence of direct source references certifying the presence at the castle of an official with any administrative prerogatives beyond the castle itself (i.e. exercising territorial authority) the article indicates a number of indirect premises against the thesis about the functioning of a Kämmerer’s office in Bezławki, as well as its possible translocation in the period between the construction of the castle, most probably in the second half of the 1370s, and 1437. Considering the result of the analysis, it should be presumed that the stronghold was supervised at that time by an administrator called the “burgrave”, who, although not a member of the Teutonic Order, was a member of a group belonging to this religious corporation.